1994
DOI: 10.1007/bf01830240
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use and prostate cancer in Blacks and Whites in the United States

Abstract: Prostate cancer occurs more frequently in Blacks than Whites in the United States. A population-based case-control study which investigated the association between tobacco use and prostate cancer risk was carried out among 981 pathologically confirmed cases (479 Blacks, 502 Whites) of prostate cancer, diagnosed between 1 August 1986 and 30 April 1989, and 1,315 controls (594 Blacks, 721 Whites). Study subjects, aged 40 to 79 years, resided in Atlanta (GA), Detroit (MI), and 10 counties in New Jersey, geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
167
4
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(181 citation statements)
references
References 7 publications
6
167
4
4
Order By: Relevance
“…Further studies should include other populations, such as Blacks, in whom prostate cancer rates are higher (Hayes et al, 1999;Gronberg, 2003), to extend the generalisability of the present findings. …”
Section: Discussionmentioning
confidence: 72%
“…Further studies should include other populations, such as Blacks, in whom prostate cancer rates are higher (Hayes et al, 1999;Gronberg, 2003), to extend the generalisability of the present findings. …”
Section: Discussionmentioning
confidence: 72%
“…28,29 Recent studies have reported that high fat diets could alter steroid hormone profile 30,31 and overcooked red meats contain high amounts of heterocyclic amines, 22,23 both of which are suggested to increase advanced prostate cancer risk. 32 Contradictory to an earlier result, 5 it was recently concluded that dietary fat rather than red meat was associated with PCa. 33 In the present study, we did not find a statistically significant association between meat intake, PhIP, MeIQx, and prostate cancer (Tables 2-4).…”
Section: Discussionmentioning
confidence: 96%
“…Among the biologic differences, higher levels of circulating androgens [12] and proportions of susceptibility alleles in the metabolism pathways for androgens [13] may contribute to greater disease burden in AA men. An important environmental factor is the high consumption of animal fat, which is reported to be both common in AA diets and associated with increased risk of PCa [14]. Moreover, AA men may suffer more from traumatic stress related to PCa than non-AA men [15,16].…”
Section: Discussionmentioning
confidence: 99%